(untitled) (Jurnal Teknologi Industri Pertanian, 2023)
Moringa leaves (Moringa oleifera) have bioactive components such as phenolic compounds, which have antioxidant activity and are beneficial for health, such as preventing free radicals, anticancer and antidiabetic. Bioactive ingredients from Moringa leaves have weaknesses namely, they are sensitive to heat, light, and oxygen, so an encapsulation process is needed to minimize the loss of bioactive compounds in the extract. This study aimed to determine the effect of coating ingredients from maltodextrin and Whey Protein Isolate with ratios (1:3 and 3:1) on the characteristics of Moringa leaf extract microcapsules. This research is descriptive research with three repetitions. Dried moringa leaves were extracted using ethanol solvent with the Ultrasound-Assisted Extraction (UAE) method. The extract obtained was encapsulated and spray-dried at an inlet temperature of 125°C. The results showed that Moringa leaf extract had a phenolic content of 590.25 ± 1.12 (mg GAE/g), a flavonoid content of 173.96 ± 1.57 mg QE/g and an IC50 value of 52.74 µg/mL. The combination of maltodextrin and whey protein isolate (WPI) coating materials with ratios (1:3 and 3:1) produced yield values (53.66 ± 2.25 % and 60.78 ± 4.60%), water content (3.49 ± 0.35 % and 3.73 ± 0.4 %), solubility (95 ± 0.03% and 86 ± 0.08 %), total phenolic (377.21 ± 0.82 mg GAE/g and 349.88 ± 1, 64 mg GAE/g), total flavonoids (101.32 ± 3.36 mg QE/g and 86.35 ± 2.81 mg QE/g), IC50 (88.22 ± 0.68 µg/mL and 149, 65 ± 4.03 µg/mL) and encapsulation efficiency (63.94% and 59.31%) and the resulting colour leads to a green colour. Keywords: Moringa leaves, maltodextrin, microcapsules, whey protein isolate